Serum 25-hydroxyvitamin D status and vitamin D supplements use are not associated with low back pain in the large UK biobank cohort - Sha, Sha; Chen, Li-Ju; Brenner, Hermann; Schöttker, Ben (Nutrients, 2024)
Longitudinal studies assessing the association of vitamin D deficiency, defined by serum 25-hydroxyvitamin D levels < 30 nmol/L, and vitamin D supplement (VDS) use with low back pain (LBP) are sparse. This investigation assessed the cross-sectional and longitudinal association of vitamin D status and VDS use with LBP among 135,934 participants from the UK Biobank cohort. Approximately 21.6% of the participants had vitamin D deficiency, while only 4% regularly took VDS. In the month before study enrollment, 3.8% of the population reported experiencing LBP. An additional 3.3% of the population were diagnosed with LBP by their general practitioners for the first time during a median follow-up of 8.5 years. Vitamin D deficiency and VDS use were cross-sectionally associated with LBP in age- and sex-adjusted models, but these associations were not evident in comprehensively adjusted models. In longitudinal analyses, both vitamin D deficiency and VDS use were not associated with LBP in any model after correction for multiple testing. In conclusion, not unexpectedly due to the fact that LBP is multifactorial, our findings provide no evidence for the role of the vitamin D status in the etiology of LBP.